Signs and Symptoms in persons that living with HIV/AIDS. (Colombia Medica, 2007)
Introduction: The experience of symptoms by persons that live with the AIDS virus has influence on the adherence to antiretroviral (ARV) treatment, quality of life, and potential transmission of VIH. Objectives: To describe demographic, clinic and personal characteristics and habits of persons with HIV/AIDS that attend ambulatory health care services at Cali, Colombia. To recognise frequency and intensity of symptoms and signs that experiences persons with HIV/AIDS. To establish if there are differences between some demographics and clinical characteristics of HIV/AIDS patients with the symptoms´ experience. Methodology: Descriptive cross-sectional design; it was applied to 137 persons living with the AIDS virus an instrument about demographic and clinical characteristics and a sign & symptoms check list. Results: The age mean was 35 years, 70% were masculine, 88% had some type of health insurance and 64.2% received ARV treatment. The more frequent signs & symptoms reported were thirsty, fear/worries, muscle aches, weakness, fatigue and depression. Persons living with HIV/SIDA have many psychological symptoms that determine the necessity of assess carefully the adjective of «asymptomatic» that caregivers gave to them. Conclusion: Most persons living with HIV/SIDA had mental symptoms. Those emotional signs and symptoms can be explained because of the loss of health. Nurses as caregivers should give care based on their own models that involves family and others health care personal, and self-care for those patients.